Occurrence and distribution of polyhalogenated carbazoles in eastern Tibetan Plateau soils along the slope of Mt. Qionglai. (July 2022) - Liu, Mingkai; Huang, Longhua; Li, Xiaoshuang; Liu, Fei; Zhang, Wei; Wang, Zhe; Xu, Yan; Ke, Runhui; He, Hongping; Lou, Yinghua
Abstract: Polyhalogenated carbazoles (PHCZs), are considered as potential persistent organic pollutants (POPs), which have been frequently detected in the environment. However, the altitudinal distribution characteristics and possible sources of PHCZs in high mountain soils are still unknown. The present study was the first to analyze PHCZs in soil samples collected along the eastern slope of Mt. Qionglai (MQ), the east edge of the Tibetan Plateau. The concentration of ΣPHCZs (based on dry weight) ranges from 14.4 to 107 ng/g (median value of 40.9), which was at high end of the range reported in soils and sediments to date in the literature. The composition profiles of PHCZs in the soils of MQ were dominated by 3, 6-dichlorocarbazole (36-CCZ), 3-chlorocarbazole (3-CCZ), and 2-bromocarbazole (2-BCZ). The mean TOC-normalized concentrations of ΣPHCZs in soil samples from below-treeline (2092 ng/g TOC) were higher than those from alpine meadow (1124 ng/g TOC), probably due to the forest filter effect. The decreasing trend of the PHCZs TOC-normalized concentrations with altitude shows that accumulation of PHCZs from the alpine meadow samples was not affected by the mountain cold-trapping effect. Significantly positive correlations were observed between the concentrations of more than half of detected PHCZ congeners and TOC. In addition, PHCZs show the potential to represent a class of POPs with the frequent occurrence and wide distribution, as the abundance and environmental behavior of PHCZs are similar to some POPs in MQ. Graphical abstract: Image 1 Highlights: PHCZs were detected in Tibet Plateau soil for the first time. PHCZs levels in Mt. Qionglai soils are higher than those in soils and sediments reported so far. The mountain cold-trapping effect on PHCZs in the alpine meadow is not obvious. TOC may have an important effect on the environmental behavior of most PHCZs.